A Qualitative Analysis of Rural Community Vaccination Barriers During the COVID-19 Pandemic - Kimberly C. McKeirnan; Megan R. Undeberg; Skylar Zelenko; Ghazal Meratnia (Vaccines)
Background/Objectives: Rural communities in the United States experience increased disparity of care for both general healthcare services and access to routine vaccines. Previous research has indicated a 40% lower vaccination rate in rural communities, as compared to urban counterparts. Having a better understanding regarding factors influencing lower vaccination rates in rural areas could help public health officials prepare for future vaccination efforts. This research sought to gather and evaluate the opinions of people who live and work in rural areas regarding barriers to COVID-19 vaccine uptake. Methods: A semi-structured qualitative key informant interview design was utilized by researchers to gather opinions from university Extension staff in Washington State. Interview transcripts were analyzed using the Theory of Planned Behavior (ToPB) framework to evaluate COVID-19 vaccination-related intentions and motivational factors that the Extension staff observed among rural populations in their communities. Results: Twenty-one participants representing 34 out of the 40 Extension offices responded and were interviewed during fall 2023. Using the ToPB constructs, nine barriers were identified. Attitude-related barriers included the following: inherent social distancing in rural location negating vaccine necessity; lack of early vaccine availability in rural locales; concerns regarding ineffectiveness of the vaccine; and inadequate dissemination of vaccine information to non-English language speakers and those with limited access to technology. Subjective norm barriers included the following: perception of exclusion of rural populations’ unique needs during design and implementation of vaccine mandates; exertion of social pressures on rural individuals’ vaccine uptake decision; and highly visible breakdown in standard trust in core community institutions and leadership. Barriers related to loss of perceived behavioral control included vaccine mandates impacting self-perceived loss of autonomy and limitations in vaccine technology information impacting perception of vaccine safety. Conclusions: By identifying barriers to vaccination in rural communities during the COVID-19 pandemic, future outreach efforts can be designed to improve intention and lead to stronger vaccination uptake.